Energy Analysis of a Hybrid Solar Dryer for Drying Coffee Beans - Suherman Suherman; Hasri Widuri; Shelyn Patricia; Evan Eduard Susanto; Raafi Jaya Sutrisna (International Journal of Renewable Energy Development, 2020)
In this study, hybrid solar drying of coffee beans was performed, and energy analysis was carried out, to assess the system’s performance, in terms of energy efficiency, compared to solar drying and the open sun drying method. The dryer has three compartments: solar collector for collecting solar radiation, drying chamber, and a Liquid Petroleum Gas burner, which acted as an auxiliary heater to assist the thermal energy. The drying chamber has four trays for placing the dried product. The initial moisture content of coffee beans was 54.23% w.b and was reduced to the final moisture content between 11-12% w.b. The coffee beans dried faster when subjected to the solar hybrid drying method, compared to other methods, with the dryer temperature of 40°C, 50°C, and 60°C. Results indicated that the coffee beans’ drying times varied from 10 to 14 hours. However, at temperature 50°C and 60°C for the 1st tray, the water content was reduced more rapidly compared to the other tray. From the results of this study, we can see the different efficiency of solar collector that shows of 54.15% at variable temperature 60°C for drying time 12:00 to 14:00 p.m for hybrid solar drying and for the solar drying process is 50.07% at the range of drying time 12:00 to 14:00 p.m. Mathematical modelling shows that Page model is the most suitable for describing the coffee beans’ drying behaviour using a hybrid solar dryer. The effective diffusivity values found in this experiment are all in the acceptable range for most agricultural products. ©2020. CBIORE-IJRED. All rights reserved